A systematic review on the effectiveness of herbal interventions for the treatment of male infertility - Shahid, Muhammad Nabeel; Afzal, Hassaan Shahzad; Farooq, Bareerah; Yousaf, Muhammad Rehan; Ijaz, Muhammad Rauf; Shafqat, Talha Ali; Khan, Tahir Mehmood; Neoh, Chin Fen; Lean, Qi Ying; Bukhsh, Allah; Karuppannan, Mahmathi (Frontiers in Physiology, 2022)
Background: Male infertility is an emerging health issue in the world today. Surgical interventions for the treatment of male infertility are available but are quite expensive. Herbal interventions pose a popular alternative for the treatment of infertility. However, much has to be learned regarding their safety and efficacy. Objective: The aim of the study was to investigate the efficacy of herbal interventions in male infertility and also assess the possibility of these interventions as complementary and alternative medicine (CAM) in the future. Method: From inception until 16 December 2021, all articles emphasizing the efficacy of herbal interventions in the treatment of male infertility are included in this review. Seven databases are searched. The literature obtained is screened and extracted. Semen parameters, hormonal concentration, and conception are the outcomes of interest. Results: A total of 19 articles were included in this review. Herbal interventions might improve semen parameters in males with infertility. Among all the interventions, Hochu-ekki-to and W. somnifera have shown the most promising results and should be studied further in a larger sample size. Conclusion: This systematic review has demonstrated the efficacy of herbal interventions, especially Hochu-ekki-to and W. somnifera, in treating male infertility.